2007
DOI: 10.1097/01.anes.0000264749.86145.e5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deaths Related to Anesthesia in the Period 1996–2004 from Closed Claims Registered by the Danish Patient Insurance Association

Abstract: Several of the 24 deaths could potentially have been avoided by more extended use of airway algorithm, thorough preoperative evaluation, training, education, and use of protocols for diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 9 publications
1
54
0
2
Order By: Relevance
“…Although the majority of evidence suggests that combined anesthesia reduces the number of deaths [19][20][21][22] , one previous study has demonstrated increased mortality among patients given this type of anesthesia 23 . Obese patients are susceptible to ineffective coughing, basal atelectasis and progressive hypoxia, facilitating infection 13 .…”
Section: Discussionmentioning
confidence: 98%
“…Although the majority of evidence suggests that combined anesthesia reduces the number of deaths [19][20][21][22] , one previous study has demonstrated increased mortality among patients given this type of anesthesia 23 . Obese patients are susceptible to ineffective coughing, basal atelectasis and progressive hypoxia, facilitating infection 13 .…”
Section: Discussionmentioning
confidence: 98%
“…A closed claims study analyzing deaths related to anesthesia in the period 1996 -2004 in Denmark did not identify any cases of suspected perioperative anaphylaxis leading to a claim in the patient insurance association. 35 Data on mortality from anaphylaxis during anesthesia varies in the literature, but because of the rarity of these events and the many potential sources of error in obtaining mortality data, it is uncertain whether there are differences in mortality in different countries. It is, however, important to note that geographic differences exist in the causes found on investigation of anaphylaxis during anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Hove et al [50] examined claims from the Danish Patient Insurance Association, (a national no-fault compensation scheme) over a 9-year period (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004). In Denmark approximately 400 000 anaesthetic events take place per year.…”
Section: ó 2009 the Authorsmentioning
confidence: 99%